Wealth portfolio of Hungarian households - Urban legends and facts - Gábor Vadas (Magyar Nemzeti Bank, 2007)
As significant part of national wealth, households' wealth is the central issue in both policy debate and academic literature. Nevertheless, in Hungary little effort has been made so far to conduct thorough evaluation of households' wealth for the last decade. Under the auspices of the plural of anecdote is not evidence axiom, this study provides a formal evaluation of Hungarian wealth and connects the development of wealth elements to economic events. Doing so, as a by-product, we also display the estimated wealth levels of households. Based on international comparison and econometric techniques, it is confirmed that the recent financial wealth level of Hungarian households is still relatively low, meanwhile the current housing wealth is not evidently below the equilibrium level. These results provide an explanation why governmental housing subsidy scheme has its major effect on house prices rather than housing stock. Besides, the soaring house prices, via housing loans, vanished financial savings. The saving disaster, i.e. small or in some periods even negative saving rates, experienced in early 2000's, to a certain extent, is the other side of the saving miracle of early and mid 90's when households rearranged their wealth portfolio from real assets to financial assets implying decreasing house prices and high saving rate.
Keywords: E00; E21; E31; H31; 330; household wealth; housing subsidy scheme; house price; Privater Haushalt; Vermögen; Wohneigentum; Wohnungspolitik; Immobilienpreis; Ungarn; Welt